FAKTOR PEMBATAS PERTUMBUHAN DAN HASIL TANAMAN KARABENGUK (Curcuma pruriens (L) DC.) MUSIM KEMARAU PADA TANAH LATOSOL DAN LITOSOL - Marjono Marjono; Supriyono Supriyono; Supriyadi Supriyadi; Djoko Purnomo (Universitas Sebelas Maret, 2010)
Fertilizer of NPK or manure no velvet bean yield increase. On leguminosae, nitrogen fertilizer utilization can decreased rhizobium activity on nodule change N2 to ability nitrogen for plant. For this reason, experiment limiting factor for velvet bean yield important to due. This research was conduct on Litosol soil in Tancep, Ngawen, Gunungkidul regency and on latosol soil in UNS experimental Land, Jumantono, Karanganyar regency. The experimental design was Randomized complete block design and factorial with 2 factors. The treatment was: 1) soil kind, 2 level litosol soil in Ngawen and latosol soil in Jumantono, and 2) fertilizer on 7 level, a) control without fertilizer, b) P 200 kg/ha, c) P 100 kg/ha and K 100 kg/ha, d) P 200 kg/ha and foliage fertilizer D, e) P 200 kg/ha and foliage fertilizer B, f) P 100 kg/ha, K 100 kg/ha and foliage fertilizer D and g) P 100 kg/ha, K 100 kg/ha and foliage fertilizer D and B. All experiment due with 3 replications. Result of this research shows: 1) P, K and micro nutrition due to limiting growth and yield of velvet bean, 2) latosol soil take the higher growth and yield than litosol soil, 3) plant growth and yield on latosol soil was very responsive than litosol soil.